Reconstrução de rupturas induzidas no tendão extensor digital longo em pôneis, utilizando homoimplante tendíneo preservado em glicerina 98% e fio náilon monofilamentoso - Cardona, Rodrigo Otávio do Canto (2007)
The long digital extensor tendon can suffer trauma with considerable lack of a segment, becoming extremely difficult the primary repair due to muscle contraction and wound contamination. In order to correct this, an experimental model was developed, using 6 adult ponies, weighing betweem 150 to 200 kg. Before the pre surgical adaptation, the animals were submitted to a surgical procedure under general anaesthesia. Through a surgical incision in the right rear limb, a piece of 3cm in length of the long digital extensor tendon was removed. In the tendon gap was implanted an homologus tendon segment preserved in glyceril 98% by mean of a Kessler modified suture, with mononylon 2.0. In the other limb was done a similar defect with excision of 3cm of the same tendon, repaired only with Kessler modified suture, leaving the mononylon strands in the gap, without the use of preserved homograft. After the surgical procedure, an external restraint with acrylic device was applied in both rear legs for a period of 60 days. Ninety days after the surgery all animals went under a new procedure in which, there were done biopsies of both repaired tendons. Besides they went thought histological analysis. It was verified that there was a good healing in both repairing methods. The tendon that was grafted presented advantages such as the dimensions maintenance of the receptor tendon. As well as the peritendineous adherence missing. As for the limb function there was not observed any change, so all animals, regardless of the repairing methods, presented a perfect motion in different trails level.